2007
DOI: 10.1111/j.1462-5822.2007.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ag85B protein of Mycobacterium tuberculosis may turn a protective immune response induced by Ag85B-DNA vaccine into a potent but non-protective Th1immune response in mice

Abstract: Clarifying how an initial protective immune response to tuberculosis may later loose its efficacy is essential to understand tuberculosis pathology and to develop novel vaccines. In mice, a primary vaccination with Ag85B-encoding plasmid DNA (DNA-85B) was protective against Mycobacterium tuberculosis (MTB) infection and associated with Ag85B-specific CD4+ T cells producing IFN-gamma and controlling intramacrophagic MTB growth. Surprisingly, this protection was eliminated by Ag85B protein boosting. Loss of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 46 publications
3
51
0
Order By: Relevance
“…Thus, in this study, we evaluated the protective responses of DNA vaccines in the spleens and lungs following MTB infection. Vaccinated mice were infected with 1x10 5 CFU of the MTB H37Rv strain. Approximately 3 months later the bacillary burden in the spleens and lungs was detected, and it was identified that the bacterial burdens in Ag85B/T-bet-vaccinated mice were lower than in the empty vector mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, in this study, we evaluated the protective responses of DNA vaccines in the spleens and lungs following MTB infection. Vaccinated mice were infected with 1x10 5 CFU of the MTB H37Rv strain. Approximately 3 months later the bacillary burden in the spleens and lungs was detected, and it was identified that the bacterial burdens in Ag85B/T-bet-vaccinated mice were lower than in the empty vector mice.…”
Section: Discussionmentioning
confidence: 99%
“…Three months after the last immunization, different groups of mice were challenged intravenously at the tail vein with 1x10 5 CFU of the MTB H37Rv strain. The mice spleens and lungs were dissected on weeks 1, 2, 4 and 8.…”
Section: Mtb Infection and Colony-forming Unit (Cfu) Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the efficacy of DNA vaccines is limited due to problems related to delivery, animal species and degradation of plasmid DNA, resulting in modest cellular and humoral immune responses. In the past years, DNA vaccines also have been studied against tuberculosis in animal models [11][12][13][14][15][16]. These DNA vaccines encoding Ag85A/B/C, ESAT-6, MPT64, PST1/2/3, 38 kDa or HSP70, when used individually or in combination, have conferred inferior or similar to protection against M. TB challenge than that of BCG.…”
Section: Introductionmentioning
confidence: 99%